An analytical Review of Online Education in India: Challenges and Prospects - Shekhar Misra, Shashi (International Journal of Psychosocial Rehabilitation, 2020)
It is inevitable that the education sector would be affected by rapid technological progress. Many studies are being conducted to determine the advantages and disadvantages of online education vs. traditional classroom instruction. Online education in India faces both difficulties and prospects. Online education in India is expected to grow in popularity thanks to a thorough literature evaluation in this research. We’ve established that internet penetration, low-cost online education, convenience of course completion, government initiative, employer recognition, and bridging the gap are all important variables in the rise of online education. Insufficient digital infrastructure, lack of legitimacy, and the language used in online education are some of the challenges that are hampering progress. The article also examines the future of education in India in light of the country’s growing internet population.